The late stages of the Pampean Orogeny, Córdoba (Argentina): Evidence of postcollisional Early Cambrian slab break-off magmatism. (December 2015) - Ramos, Victor A.; Escayola, Mónica; Leal, Pablo; Pimentel, Marcio M.; Santos, João O.S.
Abstract: Widespread rhyolitic and mafic volcanism in the northern and southern sectors respectively of Eastern Sierras Pampeanas, central western Argentina, are associated with an important phase of extension and uplift linked to slab break-off on latest stages of the Pampean Orogeny. The main orogenic deformation took place between 540 and 535 Ma based on new ages available for this region. New U–Pb ages in zircons from the Oncán Rhyolite and new and old recalculated zircons from Los Burros Rhyodacite in the northern sector of Sierras de Córdoba, together with new U–Pb ages of the southern sector, indicate that volcanic and subvolcanic rocks of both sectors are partially coeval and unconformably overlying and/or intruding the basement rocks during a period of exhumation and subsequent cooling at 530-520 Ma. These data are in agreement with previous estimates for the final uplift of the Sierras de Córdoba based on the K–Ar cooling ages. The southern sector of Eastern Sierras Pampeanas may represent deeper structural levels within the crust and is characterized by the occurrence of small mafic bodies with OIB-like signature. New and reinterpreted U–Pb SHRIMP and TIMS ages on zircons and monazites in the metamorphic associated rocks date this episode, which is related to a rapid slab break-off event at 519-515 Ma. This episode is also associated with the emplacement of peraluminous granitoids, and with the extension, cooling and final uplift of the rocks affected by the Pampean Orogeny all along the Eastern Sierras Pampeanas. Graphical abstract: Highlights: Widespread rhyolitic volcanism postdated the Pampean Orogeny. The Pampean Orogeny took place at the Neoproterozoic-Cambrian boundary. Petrological and structural evidence point out to an important slab break-off perod. The deeper structural levels at the lower middle crust are related to mafic rocks.